Word-specific and word-general knowledge in L2 Chinese lexical inference: An exploration of word learning strategies. (December 2019) - Zhang, Haomin; Koda, Keiko; Han, Yuting; Lin, Jiexin
Abstract: Drawing on Kieffer and Lesaux's (2012) categorization of word knowledge, the current study explored word-specific and word-general knowledge in second language (L2) Chinese lexical inferencing ability. L2 Chinese study-abroad students ( N  = 228) participated in the study and completed a series of word-specific (morpheme recognition and morpheme discrimination) and word-general (character knowledge and definitional knowledge) measurements. The multivariate path analysis found that word-specific and word-general knowledge collectively contributed to L2 Chinese lexical inference. In addition, definitional knowledge and morpheme discrimination were found to have the strongest predicting power. More important, the study suggests that there is a potential bidirectional relationship between word-specific and word-general knowledge in Chinese word-knowledge development. Both theoretical and pedagogical implications were discussed. The findings theoretically verified one of the underlying mechanisms of L2 Chinese lexical inferencing and also indicated that potential independent or moderating factors could be explored in future studies. Pedagogical implications focused on the explicit instruction of word-learning strategies (metalinguistic awareness and lexical inferencing strategies).